Characterising the individual performance responses to mild illness in international swimmers. Issue 10 (23rd September 2005) - Pyne, D B; Hopkins, W G; Batterham, A M; Gleeson, M; Fricker, P A
Abstract : Objectives: To determine individual differences in the impact of illness on the change in performance of swimmers in international competitions. Methods: Subjects were members of the Australian swimming team ( 33 male and 39 female, aged 15–27 years). Swimmers provided a weekly seven day recall of symptoms of illness during final six weeks of preparations for international competition over a three year period. Swimmers were categorised as either ill (one or more episodes of illness) or healthy. The measure of performances was the international point score. Mean changes in points score were calculated for healthy and ill swimmers between a national championship and an international competition (∼16 weeks later). Likelihoods of substantial effects of illness on an individual's true change in performance (beneficial/trivial/harmful) were estimated from means and standard deviations, assuming a smallest substantial change of 6 points. Results: Illness was reported before international performances by 38% of female and 35% of male swimmers. For female swimmers the change in performance was −3.7 (21.5) points (mean (SD)) with illness and −2.6 (19.0) points when healthy; for male swimmers the changes were −1.4 (17.5) points with illness and 5.6 (13.2) points when healthy. The likelihoods that illness had a substantial beneficial/trivial/harmful effect on performance of an individual swimmer were 32%/31%/37% for female and 17%/31%/52% for male participants (90% confidence limits ∼±10% to 20%). Conclusions: Although mild illness had only a trivial mean effect on female swimmers and a small harmful mean effect on male swimmers, there were substantial chances of benefit and harm for individuals.